Now playing at the Valencia Pulitzer Prize-winning essays on movies - Hunter, Stephen 1946-
Evanston, Illinois, was an idyllic 1950s paradise with stately homes, a beautiful lake, a world-class university, two premier movie houses, and one very seedy movie theater--the Valencia.